2020
DOI: 10.1038/s41467-020-17987-8
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to air pollution and scarlet fever resurgence in China: a six-year surveillance study

Abstract: Scarlet fever has resurged in China starting in 2011, and the environment is one of the potential reasons. Nationwide data on 655,039 scarlet fever cases and six air pollutants were retrieved. Exposure risks were evaluated by multivariate distributed lag nonlinear models and a meta-regression model. We show that the average incidence in 2011-2018 was twice that in 2004-2010 [RR = 2.30 (4.40 vs. 1.91), 95% CI: 2.29-2.31; p < 0.001] and generally lower in the summer and winter holiday (p = 0.005). A low to moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 42 publications
0
22
1
Order By: Relevance
“…Liver injury triggers KC activation, leading to the release of inflammatory cytokines and chemokines, such as IL‐1β and TNF‐α (Tacke, 2017). KC‐derived IL‐1β increases hepatocyte NF‐κB signalling, which interferes with FXR and NR1H3 binding to the corresponding promoters of genes for canalicular bile transporters ( Abcc2 and Abcb11 ) and sterol transporters ( Abcg5/8 ), resulting in transcriptional suppression and subsequent cholestasis (Liu et al, 2020). Taken together, tectorigenin can indirectly protect liver parenchymal cells by inhibiting KC activation and KC‐derived IL‐1β.…”
Section: Discussionmentioning
confidence: 99%
“…Liver injury triggers KC activation, leading to the release of inflammatory cytokines and chemokines, such as IL‐1β and TNF‐α (Tacke, 2017). KC‐derived IL‐1β increases hepatocyte NF‐κB signalling, which interferes with FXR and NR1H3 binding to the corresponding promoters of genes for canalicular bile transporters ( Abcc2 and Abcb11 ) and sterol transporters ( Abcg5/8 ), resulting in transcriptional suppression and subsequent cholestasis (Liu et al, 2020). Taken together, tectorigenin can indirectly protect liver parenchymal cells by inhibiting KC activation and KC‐derived IL‐1β.…”
Section: Discussionmentioning
confidence: 99%
“…NO 2 is mainly emitted into the air by burning fossil fuels, especially vehicle fuels. O 3 is formed by the interaction of nitrogen oxides (NOx) and volatile organic compounds (VOCs) with sunlight and it is also high positive correlation with vehicles exhaust emissions 35 . Using gasoline or diesel fuel cars and using carbon compounds in industrial processes are the major two responsibilities for CO being discharged to the atmosphere 36,37 .…”
Section: Description Of the General Conditionmentioning
confidence: 99%
“…The Yangtze River Delta is one of the top five regions affected by COVID-19 in China, with 1835 and 1322 confirmed cases having been reported in Shanghai Province and Zhejiang Province, respectively, as of 16 March 2021, by local health commissions. The Yangtze River Delta is one of the most densely populated regions on earth and belongs to the more developed areas of China, with over 150 million registered residents.…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, the WHO listed 10 environmental threats to global health; of these, air pollution was considered the greatest threat [16]. Previous studies have demonstrated a positive association between exposure to air pollution and the rate of RIDs [16,17].…”
Section: Introductionmentioning
confidence: 99%